IMPACT OF CLIMATE CHANGE ON NATURAL GROUNDWATER RESOURCES OF THE CENTRAL VOLCANIC HIGHLANDS OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Armenia's drinking water supply is mainly provided by high-quality groundwater from the volcanic highlands. Over the past decade, there has been a constant decline in the flow of springs, which is due to a decrease in precipitation. The main role in the formation of groundwater is played by precipitation in the recharge zone – at absolute elevations above 2500 m. Groundwater formation occurs in fractured volcanic rocks, and accumulation and movement occur in buried river valleys. Various scientific and political organizations have developed models for climate change projection under various scenarios (IPCC, METRAS), which were used by various public organizations to simulate climate change until 2100 for the territory of Armenia and published in the form of national communications. A comparative analysis of the data obtained in the work with the IPCC reports showed that the forecasts of various IPCC scenarios are not reliable. And METRAS forecasts indicate that the lack of factual material complicates the accuracy of calculations. To find out the relationship between precipitation in the recharge area and the flow rate of springs, the approximate groundwater residence time was calculated using the pattern of the Arzakan springs, where the groundwater travel distance is 24 km and the estimated time was calculated as 6.5 years. It was found that from 2013 to 2023, the flow rates of springs decreased according to a linear dependence, and the decrease in flow rates was 24–33%. Changes in the chemical composition of spring waters due to a decrease in flow rates have not been established, except for sulfate ion, the concentration of which increases with increasing flow rates of springs. The assumption that an increase in the content of sulfate ions may serve as a precursor of an increase in the flow rate of springs requires further research. Based on the research results, it is assumed that based on the amount of precipitation in the high-mountain zone, it is possible to reasonably project the groundwater flow rate for the studied springs for upcoming 6–7 years.